Studying the effect of high-power coherent terahertz pulses on mesenchymal stem cells. (January 2019) - Sitnikov, D S; Ilina, I V; Pronkin, A A; Ovchinnikov, A V; Chefonov, O V; Zurina, I M; Gorkun, A A; Kosheleva, N V
Abstract: Question of safety of THz radiation for living objects (starting at the cellular level and ending with the organism in whole) is still a matter of controversy and requires further study. In this paper we present experimental results of studying the effect of terahertzh laser pulses on monolayer cell culture. Bone marrow mesenchymal stem cells are exposed to multiple (from 50 to 4200) THz pulses with intensities of about 10 MV/cm. No short-term effect is observed 24 h after cell irradiation.